Relationship of Family Support with Quality of Life in Glaucoma Patients - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Biastika Alun Sukma (NurseLine Journal, 2021)
Glaucoma is incurable but can be controlled with lifelong treatment. In addition, decreased visual function affects daily activities and can reduce the quality of life of patients. A factor influencing the quality of life is family support. Family support can improve the quality of life for example, the family helps care costs. This study aims to analyze the relationship of family support with the quality of life of Glaucoma patients at Baladhika Husada Level III Hospital in Jember, using a cross sectional approach, the independent variable is family support and dependent quality of life. 71 research samples with purposive sampling. Data collection uses a family support questionnaire to assess family support and a GQL-15 questionnaire to assess quality of life. Analysis of the relationship of family support with quality of life using Spearman rank test with p value of <0.05. The results showed the percentage of family support 59 (83.1%) had high family support and 12 (16.9%) low family support, the percentage of quality of life was 58 (81.7%) had a good quality of life and 13 (18, 3%) poor quality of life. There is a relationship between family support and quality of life (p value = 0.001 r value = +0.467) with a positive correlation means the higher the family support, the higher the quality of life. Family support is related to quality of life in glaucoma patients because family support has an important role in efforts to improve quality of life.